Stingless bee honeys from Soconusco, Chiapas: a complementary approach - Espinoza-Toledo, Cristina (2018)
Stingless bees are located in the tropic areas, and produced a sweet natural substance called pot honey, with different properties and uses. Recently, most studies are focused on characterizing them, in order to contribute to their knowledge and the establishment of quality laws. Thus physicochemical, acceptance and palynological studies were performed in stingless bee honeys from Soconusco, Chiapas, in order to learn and contribute to their knowledge in the Tropics. Nine honey samples were collected from Melipona solani (Ms), M. beecheii (Mb) and Scaptotrigona mexicana (Sm) in different meliponaries. Our results registered physico-chemical values that ranged as follow; pH 2.8-4.8, electrical conductivity (EC) 114-1211 μS/cm, free acidity 24-100 meq/kg, aw 59-71 g/100g, moisture 35-38 %, color 0.13-0.75 Pfund scale, reducing sugars 47-71 %, hidroxymethylfurfural (HMF) not determined – 2.72 mg/100g, and diastase activity 1.92-11.22 DN. On the other hand, the principal component analysis (PCA) of physicochemical values showed that 86.9 % of the total variability between species was explained by the following parameters aw, moisture, free acidity, color, pH, sugars and EC. Sm honeys were associated (PCA) with a higher water content, free acidity and darker colors, while Melipona honeys with a sweeter taste and a lower diastase activity; thus honeys could be grouped by genera. The acceptance test showed that 78 % of honeys were preferred, being the SmCa sample in the category “I likely dislike” due to the bitter taste (disapproved by consumers). The melisopalynological results showed that M. beecheii honeys are monofloral with a 45 % of Fabaceae pollen, while Melipona solani and Scaptotrigona mexicana honeys are multi or polyfloral with diferent pollen types; Fabaceae, Melastomataceae, Malvaceae and Asteraceae. From this complementary study we can asume that it is necessary to implicate researchers with producers, so they could have accesss to stingless bee honey analysis and to help them to improve meliponaries management by identifying and introducing stingless bee flora.